U.S. Monetary Policy Shock Spillovers : Evidence from Firm-Level Data - Arbatli Saxegaard, Elif.; Firat, Melih; Furceri, Davide; Verrier, Jeanne (Washington, D.C. : International Monetary Fund, 2022)
We examine three main channels through which U.S. monetary policy shocks affect firm investment in foreign countries: (1) the balance sheet channel; (2) the financial channel of the exchange rate; and (3) the trade channel. For this purpose, we use quarterly firm-level data for 63 advanced economies (AEs) and emerging market and developing economies (EMDEs) over 1996-2016. Our results suggest an important and independent role for all three key channels. U.S. monetary policy shocks have larger effects on investment for firms that are more leveraged (balance sheet channel), for firms that have a higher share of debt in foreign currency (financial channel of the exchange rate), and for firms that operate in sectors with higher export dependence (trade channel). Back-of-the-envelope calculations suggest that the balance sheet channel is the most important channel of transmission of U.S. monetary policy shocks on aggregate firm investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Macroeconomic Aspects of International Trade and Finance; Monetary Policy, Central Banking, and the Supply of Money; Multiple or Simultaneous Equation Models; Multiple Variables; Production and Organizations